Plant-Pathogen Interaction to prevent Brassica from pathogens using PR proteins - Hada, Alkesh; Jolly, Monica; Sachdev, Archana (Indian Farming, 2015)
In agriculture, genes encoding antifungal proteins can be introduced into crops to boost their resistance against fungal pathogens. Different organisms may produce different antifungal proteins for defense against fungi. Hence, there is a diversity of antifungal proteins that exist in nature. Plant disease resistance is a complex phenomenon that most commonly occurs in a non-specific manner, as a result of multiple genes conditioning the ability of the pathogen to cause disease and enabling the plant host to mount an effective defence response. However, plant disease resistance can also be induced only in response to particular pathogen races, only in particular host plant cultivars, or only when both a specific pathogen race and plant cultivar interact. This host-pathogen specificity can be attributed to a single gene or a small number of related genes enabling the production of race-specific elicitors, host-selective toxins, or race-specific suppressors in different host pathogen systems. Specific plant disease resistance resulting from race specific elicitors is probably superimposed upon a non-specific resistance response that has been overcome in the host range of the pathogen. In contrast, host-selective toxins and race- specific suppressors most likely achieve host pathogen specificity in disease resistant through the modification or negation of an otherwise successful non-specific resistant response.